MEDIA PEMBELAJARAN DENGAN MACROMEDIA FLASH UNTUK MAHASISWA TINGKAT I PADA MATA KULIAH KAPITA SELEKTA MATEMATIKA DASAR - Dina Pratiwi Dwi Santi; Setiyani Setiyani (EduMa: Mathematics education learning and teaching, 2018)
This study aims to develop learning media with macromedia flash on the subject of kapita selekta matematika dasar. The stage of learning media development is ADD (Analysis, Design, Development). Activities at the analysis stage include needs analysis and needs identification. The design phase of the researcher carried out four activities, namely collecting references, composing text, selecting media and media design. Whereas for the development stage, namely realizing the design into a product and then being assessed by two validators with 1 media expert and 1 material expert. Data collection was carried out through learning media validation sheets and data analysis techniques were carried out in a qualitative way with descriptive methods. Through the research development process, mathematics learning tools obtained in the form of valid media were 91.5%..Keywords: ADDIE, Kapita Selekta Matematika Dasar, Relasi, FungsiÂ